Fintech Payment sebagai Moderasi dalam Pengaruh Literasi dan Sikap Keuangan terhadap Perilaku Manajemen Keuangan (Manajemen & Bisnis Jurnal, 2023)
This study aims to examine the effect of financial literacy and financial attitude on financial management behavior moderated by fintech payments. Financial management behavior is important and needs to be understood, especially by students who already have responsibility for making decisions regarding the management of their personal finances. The samples taken in this study were 292 students of the Department of Management, State University of Malang, class of 2019 and 2020 and used a purposive sampling method. The data obtained were analyzed through multiple linear regression and moderation regression analysis (MRA) using the SPSS 29 application. The results showed that financial literacy, financial attitudes, and fintech payments partially had a significant positive effect on students’ financial management behavior. Meanwhile, fintech payments as a moderating variable are able to strengthen the effect of financial literacy on financial management behavior, but fintech payments cannot moderate the effect of financial attitudes on financial management behavior